Adsorption Isotherm Characteristics of Calcium Carbonate Microparticles Obtained from Barred Fish (Scomberomorus spp.) Bone Using Two-Parameter Multilayer Adsorption Models - Nandiyanto, A.B.D. (Universiti Malaysia Perlis, 2020)
Adsorption isotherm of calcium carbonate microparticles prepared from calcined barred fish (Scomberomorus spp.) bone at temperature of 600â¦C was investigated. The experiments were done by testing adsorption ability of the prepared calcium carbonate microparticles (with sizes of 100, 125, and 250 Âµm) for adsorbing curcumin molecules (extracted from turmeric) in aqueous solution in the batch-type adsorption reactor. The adsorption results were compared with several two-parameter multilayer adsorption models (i.e. Langmuir, Freundlich, Temkin, Dubinin-Radushkevich, Flory-Huggins, FowlerâGuggenheim, and Hill-de Boer isotherm models). Hill-de Boer model is the best model in this study. The adsorption process takes place on a multilayer surface, and the adsorbent-adsorbate interaction is a physical adsorption (which confirmed and is good agreement with the results from Hill-de Boer models and suitable with Dubinin-Radushkevich, Langmuir, and Temkin models). Adsorption is carried out at different locations energetically under endothermic processes. The Gibbs free energy confirms that the adsorption is spontaneous. The results also confirmed that the smaller adsorbent had a direct impact on the increase in adsorption capacity (due to the large surface area). From all samples, the particle size of 125 Âµm has a good performance. Particles with smaller size (less than 125 Âµm) are less optimal in the adsorption process because some aggregation between particles occurs to become larger particles. Â© 2020 Universiti Malaysia Perlis. All rights reserved.